2008
DOI: 10.1590/s0103-50532008000800030
|View full text |Cite
|
Sign up to set email alerts
|

Age and time related pheromone production in coffee leafminer Leucoptera coffeella Guérin-Méneville (Lepidoptera: Lyonetiidae)

Abstract: Este estudo foi feito para determinar o padrão de produção de feromônio sexual em glândulas de fêmeas virgens de Leucoptera coffeella como uma medida indireta do comportamento de chamamento. O composto principal, 5,9-dimetilpentadecano (1) foi extraído de glândulas de feromônio de fêmeas virgens para ser usado em dois experimentos. No primeiro foi investigado o efeito do tempo na produção do feromônio (extratos de 10 fêmeas de dois dias de idade em intervalos de duas horas) e no outro foi avaliado o efeito da … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
(24 reference statements)
1
4
0
Order By: Relevance
“…We also obtained a chromatogram with a similar retention time to that reported recently by Lima et al (2008), who reported 5,9-dimethylpentadecane as the major compound extracted from pheromone glands of virgin females. Our results agree with those of Lima et al (2008) in that 5,9-dimethylpentadecane is the major component released by L. coffeella females. The Mexican population of L. coffeella released 5,9-dimethylpentadecane and 5,9-dimethylhexadecane.…”
Section: Discussionsupporting
confidence: 68%
“…We also obtained a chromatogram with a similar retention time to that reported recently by Lima et al (2008), who reported 5,9-dimethylpentadecane as the major compound extracted from pheromone glands of virgin females. Our results agree with those of Lima et al (2008) in that 5,9-dimethylpentadecane is the major component released by L. coffeella females. The Mexican population of L. coffeella released 5,9-dimethylpentadecane and 5,9-dimethylhexadecane.…”
Section: Discussionsupporting
confidence: 68%
“…Semiochemicals can be used to alter the natural reproductive behavior of insects, decreasing pest population levels (Cardé andMinks 1995, Dantas et al 2020). The CLM sexual pheromone was used to determine the pattern of pheromone production by females, as an indirect measure of the behavior calling for sexual intercourse (Lima et al 2008). However, although several previous studies have used adult sexing, none has clearly explained how to differentiate males from females, so the methodology of sexing males and females has remained unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The female production pattern of 5,9-dimethylpentadecane is related to the period of the day and the time after adult emerging from pupa [73]. The results in virgin females showed that the higher amounts of pheromone were produced in the period comprised between 4h before and 2h after dawn and in 1day-aged females.…”
Section: Semiochemicalsmentioning
confidence: 95%